Development and usability of a traditional game simulation module with augmented reality technology (AR-SiGaSTEM) in online learning to strengthen STEM skills among students - Adnan, Mazlini; Md Ibharim, Laili Farhana; Wong, Yoke Seng; Yee, I-van; Sukirman (LUMAT: International Journal on Math, Science and Technology Education, 2025)
STEM (science, technology, engineering, and mathematics) education is crucial for developing a workforce equipped for future technological demands. This study developed and evaluated the usability of an augmented reality (AR) teaching module called AR-SiGaSTEM, which applies game simulation techniques adapted from traditional games. The goal was to help teachers strengthen STEM skills among students through this innovative technology-enabled approach. The objectives were i) to identify teachers' perspectives on accepting AR-integrated teaching modules for online learning; ii) to develop an AR-SiGaSTEM module and game with content, functions and features suitable for online STEM learning; and iii) to evaluate the module's usability in teaching to enhance STEM skills across the curriculum. The study utilized design and development research methods in three phases: i) analyzing the content requirements and module design based on teachers' acceptance perspectives; ii) designing and developing the module following the ASSURE instructional model; and iii) evaluating usability with 16 STEM teachers. The AR-SiGaSTEM module targets Form One mathematics teachers. Data was collected via a Technology Acceptance Model (TAM) questionnaire and a usability questionnaire based on constructive alignment. The teachers agreed that well-designed, objective-aligned AR modules can effectively facilitate online learning. Usability testing showed the AR-SiGaSTEM module achieved high usability ratings. This educational technology module incorporates local wisdom through creative learning approaches aligned with the curriculum. It aims to develop science, technology, and innovation talents with knowledge/skills relevant to Industry 5.0, supporting Malaysia's National Science, Technology, and Innovation Policy. It exemplifies innovative pedagogical interventions to optimize creative teaching practices across STEM subjects.